Attaining simultaneous reduction in nox and smoke by using water-in-biodiesel emulsion fuels for diesel engine - Zainal Ambri, Abdul Karim; Khan, Mohammed Yahaya; Abdul Rashid, Abdul Aziz; Hagos, F. Y. (Universiti Teknologi PETRONAS, 2019)
This paper presents the study of water-in-biodiesel emulsions (WiBE) stabilized by surfactants with different hydrophiliclipophilic balance (HLB) on a single-cylinder diesel engine. The engine performance and exhaust emissions were compared against the base fuel biodiesel (B5 diesel) which contained 5% palm oil methyl ester (POME) in the diesel fuel, at a constant engine speed of 2000 rpm with different engine loads. 36 emulsion blends of B5 diesel mixed with 9%, 12% and 15% volume of water, HLB values of 6, 7, 8 and 9, and surfactant dosage of 5%, 10% or 15% by percentage volume of water added. The results exhibited 11.7% lower engine power with WiBE as compared to B5 diesel. It was also observed that WiBE produced higher in-cylinder pressure and heat release rate. WiBE with higher water content at high load condition produced up to 15.2% higher peak pressure with a significant reduction in both NOx and smoke opacity, while a moderate decrease in the exhaust temperature was recorded for WiBE. The research work proved that WiBE with 15% water content with optimum HLB value is capable of reducing up to 79% NOx and 23% smoke opacity simultaneously, due to the heat sink effect during combustion.